A study into photocatalytic degradation of methylene blue and glycerol aqueous solution over copper ferrite catalyst - Sin Wan, Lum (2015)
There is a growing concern on environmental damage arising from industrial discharge such as organic dyes from textile, paper, printing and leather sectors as well as glycerol waste from biodiesel sector. Consequently, this has generated a genuine interest to use catalytic green pathway to treat these effluents, hence the motivation behind the current work. In the current work, the photocatalyst employed was copper ferrite (CuFe2O4), which was prepared via co-precipitation method. Subsequently, the physicochemical properties of CuFe2O4 were examined using gas pycnometer, N2 physisorption to obtain Brunauer-Emmett-Teller (BET) specific surface area, Field Emission Scanning Electron Microscope (FESEM) and X-ray Diffraction (XRD). The effects of photocatalyst on the photo-degradation of 20 ppm methylene blue solution under visible light were examined over catalyst loadings of 0.5 and 1.0g/L. From the result, it can be concluded that CuFe2O4 was effective in the photo-degradation of methylene blue solution for both the catalyst loading of 0.5 and 1.0g/L. In addition, the photo-degradation of 0.5 v/v% glycerol solution was carried out with a catalyst lThe 2.0 g/L of CuFe2O4 was not effective in the glycerol solution. However, when H2O2 was added, a photo-fenton system was created and it has degraded the glycerol. The amount of hydrogen peroxide (H2O2) was therefore varied to determine the effectiveness of photo-fenton system of the catalyst in the photo-degradation of glycerol solution. The best amount of H2O2 for the glycerol solution-CuFe2O4 was 1.0 ml as it exhibited superior glycerol decomposition.